Ultrasonic study of 1-propanol glasses with various thermobaric histories during the glass–liquid transition. (January 2019) - Danilov, I V; Gromnitskaya, E L; Lyapin, A G; Brazhkin, V V
Abstract: Ultrasonic method has been used for experimental investigation of primary alcohol 1-propanol, which can be easily glassified at low temperatures. Two types of glasses with different thermobaric histories were obtained by different paths on the T–P diagram and were comparatively studied at isobaric heating during glass–liquid transition. At low temperatures, the elastic properties of glasses are different by tens of percent, but with increasing temperature the difference decreased and totally disappeared in the liquid phase.